The Transit of Mary Magdalene’s Soul in Catalan Artistic Production in the 15th Century - Elena Monzón Pertejo (Religions, 2021)
There are a great many studies on the figure of Mary Magdalene in different areas of knowledge. Nevertheless, there is a gap as regards the image of this character in Catalonia, and specifically regarding the visual representation of her soul at the moment when she died. This text aims to analyze this matter based on two Catalan altarpieces: the Altarpiece of Saint Mary Magdalene from Perella (Bernat Martorell, 1437–1453) and The Death of Mary Magdalene (Jaume Huguet, 1465–1480). The analysis has been carried out based on the postulates from the tradition of studies on iconography and iconology: the relationships between image and text, the history of the iconographic types and the magnetic power of images. The basic hypothesis is that the representation of Mary Magdalene’s soul in the 15th Century in Catalonia is visually borrowed from the iconographic type of the Dormition of the Mother of God. To test this, comparative analyses have been made of the visual representation of the two women and also of the textual sources, such as the canonical and extracanonical gospels, a variety of medieval legends and different hagiographies or vitas and sermons from the period.